Power of a woman - Bradford, Barbara Taylor (New York : HarperCollins, 1997)
A family tragedy forces successful careerwoman Stephanie Jardine to come to terms with the secrets of her past and a stormy relationship, in a novel by the author of A Woman of Substance.
70987
Keywords: Mothers and daughters -- Fiction; Women executives -- Fiction; Man-woman relationships -- Fiction; Forgiveness -- Fiction; Revenge -- Fiction; Romantic suspense novels